INTEGRATION OF MOBILE BASED QUEUING SYSTEMS - nur alam (Journal of Information Technology and Its Utilization, 2018)
The amount of time and energy that is wasted if people queue for public services is a serious problem. More ever if that queuing done by busy or sick people. Because of busyness, a person sometimes has to complete several matters at different places in short period of time. Therefore we need a queuing system that is able to integrate all queuing services so that the public can do all queuing processes with more comfort without having to cram into a queue. In addition, by integrating all community queuing services can get services in several places just by registering through one application. The working system of this application is to distribute information on service position and estimated waiting time through an application. To design the system, a survey was carried out in several public service facilities in the cities of Makassar and Gowa Regency. Beside that, literature studies also were carried out on similar papers. System analysis and design using the SDLC method include planning, system analysis and system design. It is expected that the results of this design can become a model that can be used as an appropriate reference to implement integration of mobile-based online queuing systems.